Variation of psychological and anthropometrics measures before and after dieting and factors associated with body dissatisfaction and quality of life in a Lebanese clinical sample - Chadia Haddad (BMC, 2021)
Abstract Objective The primary objective of this study was to assess a change in the psychological states (stress, self-esteem, anxiety and depression), anthropometric measurements and physical/mental quality of life before and after diet in a sample of Lebanese subjects visiting a diet clinic. The secondary objectives included the evaluation of factors associated with body dissatisfaction, mental and physical quality of life (QOL) before the intervention of the diet program and the change in quality of life after this intervention among those participants. Methods This cross-sectional study, conducted between May and August 2018, enrolled 62 participants recruited from three diet clinics. The QOL was measured using the 12-item Short Form Health Survey (SF-12) and the psychological states was measured using the following scales: The Rosenberg Self-esteem Scale, Perceived Stress Scale, Hamilton Anxiety Rating Scale and Hamilton Depression Rating Scale. Results A significant reduction in body dissatisfaction, anxiety, waist, weight and body fat and a significant increase in the physical and mental quality of life was seen after diet compared to before it (p < 0.001 for all). No significant variation in perceived stress (p = 0.072), self-esteem (p = 0.885), and depression (p = 0.353) after diet were found. Higher BMI (β = 0.440) and higher anxiety (β = 0.132) were associated with higher body dissatisfaction scores, whereas higher self-esteem (β = − 0.818) was significantly associated with lower body dissatisfaction. Higher perceived stress (β = − 0.711), higher body dissatisfaction (β = − 0.480) and being a female (β = − 4.094) were associated with lower mental QOL. Higher Physical Activity Index was significantly associated with higher mental and physical QOL (β = 0.086 and β = 0.123 respectively). Conclusion The results indicate the effectiveness of diet programs in enhancing the quality of life, psychological and anthropometric measures.